Identity Construction of Students with Special Needs on an Inclusive Campus: A Study of the Role of the LSBA Vocational Training Center - Nova, Prischa; Suskarwati, Sri Ulya; Ahmad, Ichsan (Communicare : Journal of Communication Studies, 2025)
This study examines the process of identity construction among students with special needs within an inclusive higher education context, with a focus on the role of a specialized vocational training center. Situated in a mainstream university committed to inclusive education, the London School Beyond Academy (LSBA) serves as a critical site for understanding how institutional support facilitates positive identity development. Using a qualitative case study approach, data were collected through in-depth interviews, participant observation, and document analysis. The study is analytically grounded in Michael Hecht’s Communication Theory of Identity, which conceptualizes identity across personal, enacted, relational, and communal layers. The findings demonstrate that LSBA operates as a communicative scaffold that enables students to shift from deficit-oriented self-perceptions toward skill-based professional identities. Vocational activities allow students to enact competence and agency, while supportive interactions with faculty and peers validate these performances and bridge identity gaps between self-perception and social recognition. At the communal level, LSBA fosters a strong sense of belonging and collective purpose, reinforcing a resilient shared identity. This study argues that specialized vocational centers function as “third spaces” for communicative identity work, helping students navigate and resist ableist structures within higher education. By framing vocational training as a form of identity communication, this research contributes to inclusive education scholarship and highlights the importance of sustained, communication-based programs that empower students with disabilities to claim their identities with dignity and confidence.